10th cbse maths solution for exercise 4.1 part 1

This page 10th cbse maths solution for exercise 4.1 part 1is going to provide you solution for every problems that you find in the exercise no 2.2

10th cbse maths solution for exercise 4.1 part 1

(iii) (x - 2) (x + 1) = (x - 1) (x + 3)

Solution:

   x² + 1 x – 2 x - 2  = x² + 3 x - 1 x - 3

   x² - 1 x - 2  = x² + 2 x - 3

x² - x²- 1 x - 2 x - 2 + 3 = 0

   - 3 x + 1 = 0

This is not exactly matches the general form of quadratic equation. So the given equation is not a quadratic equation.


(iv) (x - 3) (2x + 1) = x (x + 5)

Solution:

2 x² + 1 x – 6 x - 3  = x² + 5 x

2 x² – 5 x - 3  = x² + 5 x

2 x²- x² - 5 x – 5 x - 3  = 0

x² - 10 x - 3 = 0

This exactly matches the general form of quadratic equation. So the given equation is a quadratic equation.


(v) (2 x - 1) (x - 3) = (x + 5) (x - 1)

Solution:

2 x² - 6 x – x + 3  = x² - 1 x - 5 x - 5

2 x² - 7 x + 3  = x² - 6 x - 5

2 x²- x²- 7 x + 6 x + 3 + 5 = 0

x² - 1 x + 8 = 0

This exactly matches the general form of quadratic equation. So the given equation is a quadratic equation.


(vi) x² + 3 x + 1 = (x - 2)²

Solution:

x² + 3 x + 1 = x² - 2 x (2) + 2²

x² + 3 x + 1 = x² - 4 x + 4

x²- x² + 3 x + 4 x + 1 - 4 = 0

7 x - 3 = 0

This is not exactly matches the general form of quadratic equation. So the given equation is not a quadratic equation.

Related pages